INTENSITAS DAN WAKTU ESTRUS PADA BERBAGAI PARITAS INDUK SAPI PERAH FRIES HOLLAND PASCA PARTUS - Bambang Hadisutanto; Bambang Purwantara; Siti Darodjah (Politeknik Pertanian Negeri Kupang, 2012)
Profile Intensity And Estrus Time In Various Parity Fries Holland Dairy Cattle Postpartum. Parity is a period in the reproductive cycle of cattle with an indication of the amount of carrier confinement livestock. Feliciano, et al, (2003) states that the parity is classified into three parts, namely: (1) nuliparous , (2) primiparous and (3) pluriparous / multiparous.This study used one-way classification design with the observed 90 cows post-partum is composed of 30 first parity, 30 second parity and 30 third parity. Time of estrus observation data were analyzed with General Linear Model (GLM) followed by Duncan Multiple Range Test (DMRT).This study used one-way classification design with the observed 90 cows post-partum was composed of 30 first parity, 30 second parity and 30 third parity. Data observation of estrus time were analyzed with General Linear Model (GLM) followed by Duncan Multiple Range Test (DMRT).It could be concluded that the parity I, II and III with two estrus intensity (+ +), each for 63.3%, 46.7% and 73.4% and third estrus intensity (+ + +) respectively amounted to 36.6%, 53.3% and 26.6%. While the second estrus postpartum in various parity indicates a difference in means that the parity gives effect to the second estrus postpartum. While the second estrus postpartum in various parity indicated a significance difference that the parity gave effect to the second estrus postpartum. Keywords: Fries Holland, Parity, Estrus Intensity, Estrus Time